Strengthening Urban Food Resilience through a Community-Based Hydroponic Demonstration Model in a Flood-Prone Area - Adli Adli; Anton Hindardjo; Anees Janee Ali (Jurnal Pemberdayaan Nusantara, 2026)
This community service program aimed to strengthen food resilience and community capacity in the flood-prone urban area of Kedaung Kali Angke, West Jakarta, through a community-based hydroponic demonstration model. The program employed participatory training, practical demonstrations, mentoring, and international knowledge sharing involving Universitas Mercu Buana and Universiti Sains Malaysia. Activities included stakeholder coordination, installation of a Nutrient Film Technique hydroponic unit, cultivation training, monitoring, harvesting, and program evaluation. The program successfully established a permanent hydroponic demonstration unit as a community learning and food-production facility. Evaluation involving 51 respondents showed consistently high importance and satisfaction scores, generally exceeding 3.2 on a four-point scale. Participants positively evaluated the relevance, implementation, facilitator competence, participation, and benefits of the program. Continuous community management, maintenance, and periodic mentoring are recommended to sustain the hydroponic facility and support replication in other flood-prone urban communities.